Uji Efektivitas Ekstrak Kulit Manggis (Garcinia mangostana L.) terhadap Fusarium oxysporum pada Kecambah Kelapa Sawit - Tyas Dwi Chintya; Albertus Sudirman; Ersan Ersan (Jurnal Agro Industri Perkebunan, 2020)
Fusarium oxysporum is a pathogen that causes wilt in oil palm and can cause oil palm sprout decay. The study aimed to determine the effectivity of mangosteen peel extract (Garcinia mangostana L.) in inhibiting the growth of Fusarium oxysporum in vitro and in vivo. The research was conducted in November 2017 to June 2018 at the Politeknik Negeri Lampung. The method used was a completely randomized design (CRD) consisting of 5 treatments, namely the concentration of mangosteen peel extract 0% (control), 15%, 30%, 45%,and 60%. Data were analyzed using analysis of variance (ANOVA) and further tests of mean values using the LSD test. The results showed that mangosteen peel extract affected the percentage of inhibitory zone extract in Fusarium oxysporum in vitro at concentrations of 15%, 30%, and 45% respectively at 25,92%, 29,06% and 35,95%. The treatment of mangosteen peel extract also affected the percentage of disease incidence and number of leaves in in vivo testing.